MOTIVATION WITHIN THE ADMINISTRATIVE MANAGEMENT OF SMALL ENTERPRISES - Bermúdez Tacunga, Rafael (2017)
The main purpose of administrative management within small enterprises is the maximization of the profits obtained from the accomplished activity, inevitably requiring high rates of productivity in their workers, who in turn maintain varied motivations derived from both internal and external factors that determine the behavior evidenced within the performance of their functions and daily activities. From the above, the problem analyzed in the present work establishes the aspects of the administrative management that affect the motivation that small companies’ workers have for the performance of their work. The article presents a literature review on the motivational aspects that people have and a description of the factors that motivate workers in the performance of their duties. A survey was carried out on a sample of 200 plant workers and 6 operating heads working in 6 small manufacturing companies. The main results that are presented in the work are related by the varied motivations that the workers have according to the educational levels and the work environment that they possess.